2021
DOI: 10.1111/ppl.13491
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal stress in rice: Uptake, transport, signaling, and tolerance mechanisms

Abstract: Heavy metal contamination of agricultural fields has become a global concern as it causes a direct impact on human health. Rice is the major food crop for almost half of the world population and is grown under diverse environmental conditions, including heavy metal‐contaminated soil. In recent years, the impact of heavy metal contamination on rice yield and grain quality has been shown through multiple approaches. In this review article, different aspects of heavy metal stress, that is uptake, transport, signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 189 publications
(162 reference statements)
0
24
0
Order By: Relevance
“…Some are considered essential, in minimal amounts, for normal plant growth, (e.g., Cu 2+ , Mo 4+ , Ni 2+ , Se 2+ , Co 2+ , Zn 2+ and Mn 2+ ), while others have no known benefits to plants (e.g., Cd 2+ , Sb 3+ , Cr 3+ , As 3+ , Pb 2+ , Ag 1+ and Hg 2+ ) [ 209 , 210 ]. The high-level uptake of heavy metals in general is harmful [ 211 ], and in crops it can cause a reduction in yield [ 212 , 213 ]. There are several E3 ligases that have been described to be involved in the regulation of HMs stress tolerance ( Table 1 ).…”
Section: Heavy Metal Stressmentioning
confidence: 99%
“…Some are considered essential, in minimal amounts, for normal plant growth, (e.g., Cu 2+ , Mo 4+ , Ni 2+ , Se 2+ , Co 2+ , Zn 2+ and Mn 2+ ), while others have no known benefits to plants (e.g., Cd 2+ , Sb 3+ , Cr 3+ , As 3+ , Pb 2+ , Ag 1+ and Hg 2+ ) [ 209 , 210 ]. The high-level uptake of heavy metals in general is harmful [ 211 ], and in crops it can cause a reduction in yield [ 212 , 213 ]. There are several E3 ligases that have been described to be involved in the regulation of HMs stress tolerance ( Table 1 ).…”
Section: Heavy Metal Stressmentioning
confidence: 99%
“…A recent study by Akhtar [3] revealed that the water samples that were obtained from Hayatabad industrial estate (HIE), Peshawar and Gadoon industrial estate (GIE), Sawabi, Pakistan, contain large amounts of HMs that are further used to irrigate local vegetable crops. Since plants are sessile, they are often subjected to a wide range of biotic or abiotic stresses, including HM stress [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has adverse effects on plant physiology and biochemistry through osmotic stress, ion imbalance, oxidative stress, membrane tissue disorder, cytotoxicity and metabolic homeostasis (Hoque et al, 2021). Heavy metals accumulated in plants will cause serious harm to human health after ingestion (Kaur et al, 2021). Knockdown of OsNramp5 and OsLCT1 by CRISPR/Cas9 reduces cadmium (Cd) accumulation in rice (Songmei et al, 2019).…”
Section: Stressmentioning
confidence: 99%